Development of Learning Media to Enhance Students' Digital Literacy: A Bibliometric Analysis - Purwanto, Andik; Hamzah, Syukri; Wardana, Rendy Wikrama; Yanti, Fitri April; Butali, Reygan A. (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This research aims to determine the need for the development and application of learning media as an effort to improve students' digital literacy. The research method carried out is the determination of keywords, namely "digital literacy competency education" and "journal" in the Publish or Perish (PoP) software as a research data source database with the Scopus database, resulting in 157 articles from 2014-2024 and obtaining 42 articles as samples in accordance with the keyword criteria. Meta-data analysis was carried out using Mendeley and VOSViewer to visualize a bibliographic network with research variables such as the year of publication of the article, the country of publication of the journal, the name of the author of the article, and the article with the most citations. The results of the analysis show that the development and application of learning media as an effort to improve students' digital literacy is indeed needed in supporting the learning process and can be an interesting alternative method to improve student academic achievement. In addition, the results of mapping analysis using VOSviewer show several themes about the use of comic-based physics learning media such as 'university student', 'application', 'role', 'scientific literacy', and 'effect' which are still rarely researched and become the latest themes in research. So it can be concluded that the development and application of learning media as an effort to improve students' digital literacy needs to be researched again.